The Radioulnar Distance at the Level of the Radial Tuberosity. Issue 5 (10th October 2019) - Rausch, Valentin; Krieter, Jan P.; Leschinger, Tim; Hackl, Michael; Scaal, Martin; Müller, Lars P.; Wegmann, Kilian
Abstract : Ruptures of the distal biceps brachii tendon are generally treated operatively due to their loss of supination and flexion force. A mechanical impingement at the insertion of the tendon at the radial tuberosity is discussed to play a role in the etiology of this injury. The aim of this study was to present a detailed, three‐dimensional anatomical analysis of the radioulnar space at the radial tuberosity. A total of 166 imprints of the radioulnar space in neutral rotation and pronation from 84 cadaveric specimens of both arms using silicone impression material were produced for this study. Imprints were cut in slices of 3 mm and digitally measured after picture acquisition using a high‐resolution digital camera. Distances were grouped into a proximal, central, and distal groups and used for correlation to morphometric data at the elbow (radial head diameter, ulna and radius length) as well as volume calculation. The mean radioulnar distance was 8.8 ± 4.0 mm in neutral rotation and 7.8 ± 3.9 mm in pronation. In pronation, the central zone was the smallest whereas in neutral rotation the proximal zone was the smallest. The volume of the radioulnar space did not reduce significantly during pronation. Little space is provided for the insertion of the distal biceps brachii tendon especially during pronation. This could play a role in the etiology of distal biceps brachii tendon ruptures and should be considered in the fixation after rupture of the tendon. Clin. Anat., 33:661–666, 2020. © 2019 Wiley Periodicals, Inc.